Microbiology And Histo-Pathology Of Mandibulofacial Abscess In A Balb/C Mouse (Applied Biological Research, 2018)
Among the various laboratory animals, mice and rats with their extensive use in bioscience research,  have achieved an unparalleled level. These animals are no different from others with respect to the  possibilities of adventitious and opportunistic infections. These organisms usually do not cause any  clinical disease but instead causes physiological alterations rendering the animals unsuitable for  experimental studies. Although the number and prevalence of these pathogens have declined  considerably, but many are still around and may infect the colony. Facial abscess is the one among  such infections and the present report describes the microbiology and histopathology of a  mandibulofacial abscess. Earlier, a few cases of natural occurrence of maxillofacial abscesses in mice  has been reported (Lawson, 2010); however, the present case is first of its kind with dual infection of  methicillin resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa resistant against  multiple antimicrobial drugs.
Keywords: Microbiology; Histo-Pathology; Mandibulofacial